O papel do feedback corretivo de colegas no reparo de erros de aprendizes de inglês L.E. - Teixeira, Flávia Aparecida Ribeiro (2010)
The purpose of this study was to verify which of the types of corrective feedback (LYSTER & RANTA, 1997) are provided by learners to their peers during the collaborative resolution of tasks involving the negotiation of the grammatical form of the target language. Furthermore, this study also intended to investigate if tasks with different focus on form, explicit or implicit ( SPADA & RUSSELL, 2006), isolated or integrated to meaning (SPADA & LIGHTBOWN, 2008) can have any influence on the types of corrective feedback chosen by the learners to provide to their peers and if those feedbacks would promote learners repair of error in long-term. This study was based on the hypothesis that the types of corrective feedback proposed by Lyster & Ranta can also be found in learners interaction, during the collaborative resolution of tasks which focus on form, leading them to notice and repair their errors in the target language. The participants were six university students of a private college who were recorded during the resolution in pairs of two collaborative tasks which focused on form. The transcriptions of the recordings were made so that types of corrective feedback provided during the students interaction could be identified. The results show evidences that corrective feedback is present not only in teacher-student interaction, but also in student-student interaction and that the feedback provided by peers in the resolution of collaborative tasks can draw learners attention to grammatical form, leading them to reflect upon their utterances and to repair errors in the target-language.